Rapid determination of short DNA sequences by the use of MALDI-MS - Nordhoff, Eckhard (Oxford University Press, 2000)
We have developed a protocol for rapid sequencing of short DNA stretches (15–20 nt) using MALDI-TOF-MS. The protocol is based on the Sanger concept with the modification that double-stranded template DNA is used and all four sequencing reactions are performed in one reaction vial. The sequencing products are separated and detected by MALDI-TOF-MS and the sequence is determined by comparing measured molecular mass differences to expected values. The protocol is optimized for low costs and broad applicability. One reaction typically includes 300 fmol template, 10 pmol primer and 200 pmol each nucleotide monomer. Neither the primer nor any of the nucleotide monomers are labeled. Solid phase purification, concentration and mass spectrometric sample preparation of the sequencing products are accomplished in a few minutes and parallel processing of 96 samples is possible. The mass spectrometric analyses and subsequent sequence read-out require only a few seconds per template.